Reflexões sobre o provimento do diretor e a gestão democrática de uma escola pública : entre o eleito e o indicado - Oliveira, Rafael Gumiero de (2014)
This study aims to analyze how the school director elected or appointed (by indication) influences the democratic management of an elementary school. The research problem that motivated this discussion was as follows: How do two different models of indica